Plan de mejoramiento para la asociación de productores de maní Apromaní del valle de Casanga cantón Paltas - Astudillo Campoverde, Juan Carlos (2015)
In Canton following the signing of the Peace between Ecuador and Peru Binational project is created to improve the productivity of peanuts, it is for them that is was necessary to create the Cantonal Association Peanut Producers ( APROMANI ) in the Avocados Canton Loja Province. The international cooperation FACES Foundation built a processing plant peanut, with the actual results that the company created logo PRODUBIN PODUCTORES Binational Acct. Lta . To process and market peanuts. Once finished the intervention agencies outside the Association , he blamed the APROMANI Association to manage the company , who unfortunately not achieving optimum results due to poor knowledge so important challenge to overcome . The Superintendency of Companies in 2007 proceeds to declare insolvency in 2008 and proceeds to declare the company dissolved, PRODUBIN PODUCTORES Binational Acct. Lta . Reasons why this research called " IMPROVEMENT PLAN FOR PRODUCERS ASSOCIATION CANTONAL MANI " which seeks not only to fulfill a requirement for graduation from the same author , also seeks to investigate the historical process arises of it and contribute a viave proposal to solve this problem. In the present research work entitled "Improvement Plan for Peanut Producers Association" has two strategies. One Develop a recovery plan for the Association of Producers of peanut APROMANI contributing to socio- economic improvement; in which four components Socio- Organizational Strengthening, fund collection and marketing association is established. Cleaned up and operation of the processing plant peanut ; and Management- Administration, Thwo Develop a business plan for Peanut Producers Association APROMANI that allows for a sustainable activity for peanut producers in Canton avocados. The financial assessment indicates that the investment in the project is technically feasible and economically since a positive return is achieved